1985
DOI: 10.1016/s0022-5347(17)48816-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Primary Prostaglandins on Isolated Human Urinary Bladder

Abstract: The effects of primary prostaglandins (PGs) on the dome and trigone of the human urinary bladder were investigated in vitro. In the dome preparations, PGE1 (10(-9) to 10(-6) gm./ml.) showed a weak contractile effect, while PGE2 (10(-9) to 10(-6) gm./ml.) produced dose-dependent contractions. PGF2 alpha (10(-9) to 10(-6) gm./ml.) induced contractions greater than those induced by PGE1 and PGE2. In the trigone preparations, PGE1 (10(-9) to 10(-6) gm./ml.) had no effect, and PGE2 (10(-9) to 10(-6) gm./ml.) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A similar relationship has been re ported by Khanna et al [7] in in vivo rabbit detrusor smooth muscle and by Pogessi et al [8] in studies of the intravesical pressure elevation in the in vivo rabbit. In contrast, Ueda et al [10] and Abrams and Feneley [3] noted that the rank order of the magnitude of the con tractile effects of PGs on human detrusor muscle strips was PGF2« > PGE2 > PGE 1 at concentrations of 10-9 -10'6 g/ml. In the present study, the response to PGE| (10~6-1 0 -5 M) is greater in detrusor muscle from old than from young rabbits, whereas the responses to PGs E2 (10~7-10-5 M) and F2« (10-6-10-5 M) are greater in detrusor from young than from old rabbits.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A similar relationship has been re ported by Khanna et al [7] in in vivo rabbit detrusor smooth muscle and by Pogessi et al [8] in studies of the intravesical pressure elevation in the in vivo rabbit. In contrast, Ueda et al [10] and Abrams and Feneley [3] noted that the rank order of the magnitude of the con tractile effects of PGs on human detrusor muscle strips was PGF2« > PGE2 > PGE 1 at concentrations of 10-9 -10'6 g/ml. In the present study, the response to PGE| (10~6-1 0 -5 M) is greater in detrusor muscle from old than from young rabbits, whereas the responses to PGs E2 (10~7-10-5 M) and F2« (10-6-10-5 M) are greater in detrusor from young than from old rabbits.…”
Section: Discussionmentioning
confidence: 91%
“…There have been numerous studies on the effects of prostaglandins (PGs) on the smooth muscle of the uri nary bladder both in vivo and in vitro [1][2][3][4][5][6][7][8][9][10] and attempts have been made to evoke bladder contractions in man by the intravesical infusion of PGE2 [4,11], The effects of PGs are known to differ with age in human lymphocyte [12], rat testicular capsule [13] and in the colon, stomach and ileum of the guinea pig and rat [14], The effect of age on the response of urinary bladder smooth muscle to PGs has not been studied previously. The present study was designed to assess the age-dependent effects of PGs on rabbit detrusor smooth muscle.…”
Section: Introductionmentioning
confidence: 99%
“…PGs and LTs are di¡erentially synthesized in the urothelium and smooth muscle, respectively.Therefore, their natural balanced levels may be of great importance in maintaining the physiologic urothelial^mesenchymal interactions . It has been shown that the COX and 5-LO products are potent constrictors of the bladder smooth muscle where LTs appear more potent than PGs [Ueda et al, 1985;Bjorling et al, 1994]. In certain cases, PGs and LTs have shown opposing e¡ects under the same pathologic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial regulation of bladder smooth muscle contractility has frequently been reported [Ueda et al, 1985;Bjorling et al, 1994;Krasnopolsky et al, 1995]. LTs, the 5-lipoxygenase (5-LO) products and prostaglandins (PGs), and the cyclooxygenase (COX) products of arachidonate have been shown to play important roles [Ueda et al, 1985;Bjorling et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation